2009
DOI: 10.1128/mcb.00034-09
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine Phosphorylation of Grb2: Role in Prolactin/Epidermal Growth Factor Cross Talk in Mammary Epithelial Cell Growth and Differentiation

Abstract: Characterizing mechanisms regulating mammary cell growth and differentiation is vital, as they may contribute to breast carcinogenesis. Here, we examine a cross talk mechanism(s) downstream of prolactin (PRL), a primary differentiation hormone, and epidermal growth factor (EGF), an important proliferative factor, in mammary epithelial cell growth and differentiation. Our data indicate that EGF exerts inhibitory effects on PRL-induced cellular differentiation by interfering with Stat5a-mediated gene expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 38 publications
(56 reference statements)
0
24
1
Order By: Relevance
“…Previous reports suggested an inhibitory role of Grb2 Tyr 7 , Tyr 37 , Tyr 52 , and Tyr 209 phosphorylation in receptor tyrosine kinase signaling (16) (43). Instead, in our system Grb2 Tyr 160 mutation was not show to have a role in ALCL proliferation.…”
Section: Grb2 In Npm-alk Signalingcontrasting
confidence: 80%
See 1 more Smart Citation
“…Previous reports suggested an inhibitory role of Grb2 Tyr 7 , Tyr 37 , Tyr 52 , and Tyr 209 phosphorylation in receptor tyrosine kinase signaling (16) (43). Instead, in our system Grb2 Tyr 160 mutation was not show to have a role in ALCL proliferation.…”
Section: Grb2 In Npm-alk Signalingcontrasting
confidence: 80%
“…Furthermore, a recent report showed a role for tyrosine phosphorylation of Grb2 in prolactin receptor/Jak2 signaling (42). In this contest, tyrosine phosphorylation of Grb2 was shown to mediate the inhibitory signals of prolactin on the Ras/MAPK pathway, thereby allowing for the prolactin antagonism of EGFinduced cell proliferation in mammary epithelial cells (43).…”
Section: Grb2 In Npm-alk Signalingmentioning
confidence: 92%
“…B). Dephosphorylation as the activated state of GRB2 is supported by the observation that phosphorylated GRB2 down‐regulates tyrosine kinase signaling (Fig. S3).…”
Section: Discussionmentioning
confidence: 70%
“…Testing the cellular distribution of proteins containing one or more SH3 domains in the presence and absence of SPRR2a showed that GRB2, an adaptor protein involved in RTK signal transduction, translocated from the cytoplasm to the nucleus following SPRR2a induction. SPRR2a expression also resulted in dephosphorylation of cytoplasmic GRB2 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This protein is a regulatory subunit of signaling molecules and pathways whose activity is modulated by tyrosine receptor kinases, providing a link between cell surface growth factor receptors and the Ras signaling pathway [56,57]. Tyrosine phosphorylation of GRB2 interferes with the binding function of SH3 domains to SOS proteins, thereby negatively influencing transcription factor activation and proinflammatory responses.…”
Section: Signaling Transductionmentioning
confidence: 99%